Complex interactions and influence among political and administrative leaders - Christensen, Tom; Loegreid, Per (2003)
In this article we describe the influence of Norwegian executive political and administrative leaders on salient policy issues, based on a structural, a cultural-institutional and an exposure perspective. The data used are taken from a broad survey of elites conducted in 2000, focusing on undersecretaries of state, secretary generals and director generals in the ministries. The analysis reveals that political and administrative leaders are regarded as the most influential actors on salient policy issues. They are engaged in extensive and intensive inter-and intra-organizational contact networks. Their influence varies according to a political - administrative contact pattern, internal administrative structure and external media exposure. - Reproduced.
Keywords: Civil service